Corruption as a political risk factor for investors in the oil and gas industry, with specific emphasis on Nigeria : identification, analysis and measurement - Jessen, Lone (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.